Photoacoustic needle improves needle tip visibility during deep peripheral nerve block - Watanabe, Kunitaro (Sci Rep, 2021)
We developed a novel technology using the photoacoustic effect that improve needle tip visibility. We evaluated whether this technology improves needle tip visibility when performing a deep peripheral nerve block in a cadaver model. A photoacoustic needle was developed using a conventional echogenic needle with an intraluminal optical fiber. A pulsed laser sends light from a source through the fiber, which is converted to ultrasound at the needle tip using the photoacoustic effect. A nerve block expert performed deep nerve blocks using the photoacoustic needle and the ultrasound views recorded, with or without photoacoustic ultrasound at the needle tip. Needle tip visibility was evaluated by questionnaire (Likert scale 1: very poor, 5: very good) completed by anesthesiologists evaluating recorded images. The score was presented as median [first quartile, third quartile]. Statistical analysis was performed using the Wilcoxon matched-pairs signed rank test. The scores of needle tip visibility with photoacoustic ultrasound from the needle tip (4.3 [4.0, 4.5]) was significantly higher than that without photoacoustic ultrasound (3.5 [3.2, 3.8]) (p < 0.01). Ultrasound emitted at the needle tip using the photoacoustic effect improves needle tip visibility during deep peripheral nerve blocks. Clinical trial number University Hospital Medical Information Network Center Clinical Trials Registration System (UMIN000036974).